Thin-Film Silicon in Photovoltaics: The Role of Structure and Microstructure - Mullerova, Jarmila; Sutta, Pavol; Jurecka, Stanislav (Communications - Scientific letters of the University of Zilina, 2006)
Structure and microstructure of hydrogenated silicon thin films and the influence of the hydrogen dilution of silane plasma at the PEVCD deposition on the film properties were investigated. The results show that at dilution between 20 and 30 the transition between amorphous and crystalline phase occurs. The sample becomes a mixture of amorphous silicon, polycrystalline silicon with nano-sized grains and voids with decreasing hydrogen concentration at grain boundaries and post-deposition oxygen contamination. The dominance of Si-H bonds and presence of interstitial oxygen and oxygen bonded in surface Si-OH groups was observed.